How families matter : simply complicated intersections of race, gender, and work - Jackson, Pamela Braboy; Ray, Rashawn (Lexington Books, 2018)
This book explores the ways adults make sense of their family lives in the midst of the complicated debates generated by politicians and social scientists. It finds that parents and siblings cultivate a family identity that both defines who they are and influences who they become.